AGGREGATION EFFECT OF BENZOINDOSQUARAINS ON SINGLET OXYGEN GENERATION - Syniugina, A.T.; Ishchenko, A.A. (Reports of the National Academy of Sciences of Ukraine, 2023)
The effect of aggregation of benzoindosquaraines on singlet oxygen generation was investigated using electronic absorption and fluorescence spectroscopy in the presence of traps. The results demonstrate that benzoindosquarine with a hydrophobic side radical sensitizes the formation of singlet oxygen more effectively compared to its analog with a hydrophilic radical, especially as the percentage of water in DMSO and ethanol increases. This difference in sensitization efficiency is attributed to the higher propensity of the former to aggregate, in contrast to the latter. The study further reveals that the aggregate adopts a sandwich structure, which facilitates the activation of singlet oxygen sensitization through triplet-triplet energy transfer.